Integrasi Teori Ruang Terbuka Hijau Dan Teori Rekreasi Untuk Analisa Fungsi Sosial Terhadap Taman Kota Di Kota Surakarta - Prasetyo Febriarto (Universitas Muslim Indonesia, 2017)
The purpose of this study is to determine the social function with the existence of the city park in the city of Surakarta. The object of this study is the social function of four urban parks in Surakarta city, Balekambang Park, Tirtonadi Park, Banjarsari Park and Sekartaji Park. The method of analysis used in this study using descriptive explorative analysis. Done by analyzing the social function of the existence of the city park. Analyze activity activities that occur outside and inside the city park. The study was conducted to determine the social function that occurs to show the city parks of good quality and ideal of the four city parks.